Tsinghua University Green Initiative Quality Strategy and its Field Applications in Northern Technical University (NTU journal for Administrative and Human Sciences (JAHS), 2025)
Through the current study, we seek to present and analyze the Tsinghua University Green Initiative quality strategy and its field applications at the Northern Technical University, based on its importance and adoption by many international universities, as it is based on a central principle represented by the "green university" as a basic pillar adopted by the university in various daily university activities. Three dimensions are essential pillars that achieve this principle represented by (green education quality, green research quality, green campus quality), starting from a main question: Does the university under study adopt the dimensions of the Tsinghua University Green Initiative quality? We adopted the descriptive analytical approach from relevant modern sources, reports, records and interviews that document the extent of application of these dimensions, in addition to the questionnaire form. The study sample included the university president's assistants, department directors, division and unit officials and their assistants. Based on the results of the study, we presented a number of conclusions, the most important of which is that the Northern Technical University applies the dimensions adopted by Tsinghua Green University with high rates of agreement. These dimensions played a pivotal role in achieving an advanced position in the field of green universities and their official classifications. Based on the study's conclusions, we presented several proposals and their implementation mechanism for the university under study in order to enhance the application of the dimensions adopted by it, noting that the study is within the fourth goal of sustainable development, which includes ensuring equitable and inclusive quality education for all, and enhancing lifelong learning opportunities for all. The current study included four main axes, the first of which is the study methodology, the second presented the theoretical framework of the study, the third was devoted to the field aspect, and the fourth axis included the conclusions, proposals and their implementation mechanism.